Differentiate xe^x using first principle.

Deacon Hensley

Deacon Hensley

Answered question

2023-01-20

Differentiate x e x using first principle.

Answer & Explanation

enhee8iq

enhee8iq

Beginner2023-01-21Added 9 answers

Let f ( x ) = x e x thus f ( x + h ) = ( x + h ) e x + h
f ( x ) = lim h 0 f ( x + h ) f ( x ) h = lim h 0 ( x + h ) e x + h x e x h = lim h 0 x e x + h x e x + h e x + h h = lim h 0 x e x ( e h 1 ) h + lim h 0 h e x + h h = x e x + e x = e x ( x + 1 )

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?